Tafsîr Mawdhū’i li al-Sūrah; Analisis Kitab al-Tafsîr al-Mawdhū’I bayna al-Nazhriyyah wa Tatbîqi Karya Salāh ‘Abdul Fattāh al-Khālidi - Fatoni, Ahmad; Haq, Analia Millah Audina (Jurnal Studi Al-Qur'an, 2023)
The method of interpretation continues to evolve along with the development of interpretation. Contemporary scholars are now more fond of the mawdhū’i method as a systematic method in answering modern problems. Because the mawdhū’i method is a method that discusses a theme in the Koran, both in terms of terms, topics, and surahs in the Koran. One contemporary figure who is concerned with interpreting the mawdhū’i method is Shalah Abdul Fattah al-Khalidi with his commentary work entitled al-Tafsîr al-Mawdhū’i bayna al-Nazhariyyah wa Tathbîqi. So, this research wants to know the interpretation of mawdhū’i li as-Sūrah al-Qur'ani al-Khalidi in his book, and wants to analyze the methods. This research includes qualitative research with the type of library research. In gathering data, researchers referred to primary data, namely the book al-Tafsîr al-Mawdhū’i bayna al-Nazhariyyah wa Tathbîqi supported by secondary sources obtained from supporting literature, such as books, journals, and so on. The data collection technique uses documentation techniques. While data analysis using descriptive analysis method. The findings in this study are: (1) al-Khalidi divides the discussion into two, namely theory (nazhari) and practice (Tathbîqi), and (2) al-Khalidi formulates steps in explaining one sura, including mentioning the names of other surahs, the pronunciation of surah names in the Qur'an, the name of the surah ijtihādy, the time and place of the revelation of the sura, the situation of the revelation of the sura, the main purpose of the sura, the characteristics of the sura, the relationship between the surah Muhammad and the surah before and after the suadah, grouping the suras according to the theme, and explaining the hidden meanings in the suras.